Pelvic Pain in Adolescents - Smorgick, Noam; As-Sanie, Sawsan (Seminars in Reproductive Medicine, 2018)
Dysmenorrhea and noncyclic pelvic pain (chronic pelvic pain) are common in adolescents. The evaluation of teens with dysmenorrhea or chronic pelvic pain is aimed to diagnose possible gynecologic conditions (endometriosis, pelvic inflammatory disease, ovarian cysts, and obstruction of the reproductive tract) and nongynecologic conditions (irritable bowel syndrome, interstitial cystitis, and myofascial pain). The management of chronic pelvic pain in adolescents is often more complex than in adult women because both the adolescent and her parents are counseled and addressed, and her long-term emotional and physical health, fertility, and sexuality are considered. Dysmenorrhea and chronic pelvic pain are often associated with depression and anxiety in adolescents. Thus, psychosocial counseling plays an important role in the management of these patients. This review will present a systematic approach to the evaluation and treatment of dysmenorrhea and chronic pelvic pain in adolescents.
Keywords: adolescent; chronic pelvic pain; dysmenorrhea; endometriosis